Isothermal forging of titanium aluminides without beta-phase — Using non-equilibrium phases produced by spark plasma sintering for improved hot working behavior. (October 2018) - Bambach, M.; Emdadi, A.; Sizova, I.; Hecht, U.; Pyczak, F.
Abstract: This paper investigates the hot forgeability of a TNB-V5 (Ti–45Al–5Nb–0.2B–0.2C, at.%) alloy produced by spark plasma sintering (SPS) from pre-alloyed powder particles using the concept of processing maps. For the first time in this paper, to the best of our knowledge, we report the possibility of the isothermal forging of a TiAl alloy without the necessity to induce the ductile β-phase in the microstructure, by using non-equilibrium phases produced by SPS. At room temperature, the SPSed sample reveals a homogeneous equiaxed microstructure consisting of globular α2 -and γ-grains with the α2 -phase formed mainly at the necks between powder particles as confirmed by EBSD analyses. The necks contain a lower Al content and thus transform into α-phase upon heating to forging temperature. A stable plastic flow is observed for all ranges of the studied strain rates. The presence of a fine equiaxed microstructure at hot working temperature seems to ensure good workability and leads to a relatively wide processing window. The processing map reveals two safe processing windows for the studied alloy. The lower strain rate domain (10 −3 -10 −2 s −1 ) corresponding to a strain rate sensitivity value of ≈0.8 represents superplasticity of the fine and uniform (α+γ) equiaxed microstructure. The higher strain rate domain (10 −2 -10 −1 s −1, T > 1215 °C) with a strain rate sensitivity value of ≈0.45 represents dynamic recrystallization of the α-grains at elevated temperatures. The processing map also exhibits a domain of flow instability represented by the deformation conditions of T < 1215 °C and ε ˙ > 10 −2 s −1, which might result from the void formation and/or cracking. Although the TNB-V5 alloy was not designed for forging operations, the SPS process can create a homogeneous equiaxed microstructure consisting of globular α- and γ-grains decorating the interfaces and triple junctions between former powder particles leading to a good hot workability. The current study offers a new process design strategy by opening up the possibility of using local non-equilibrium conditions in the material during the forging process, which could stabilize the ductile phases locally. Graphical abstract: Image 1 Highlights: Isothermal forging of a TiAl alloy without β-phase using local non-equilibrium phases. SPS creates an equiaxed microstructure of α- and γ-grains decorating neck regions. A stable plastic flow is observed for all ranges of the studied strain rates. Dynamic recrystallization and superplasticity are the main deformation mechanisms. A new process design strategy to do hot deformation process at lower temperatures.